Aesop's fables - Pirotta, Saviour (Kingfisher, 2020)
This collection of eight fables brings Ancient Greece to life. The stories are retold with introductions that tell the reader all about Aesop's life as a slave and a storyteller, and explain the inspiration that lies behind his best-loved tales. Glorious illustrations by Richard Johnson complement Saviour Pirotta's warm and lively style, making this a collection to treasure. It includes stories such as: "The Cat's Bell"; "The Dog and the Wolf"; "The Lion and the Mouse"; "The Goose who Laid the Golden Egg"; "The Fox and the Crane"; "The Tortoise and the Hare"; "The Frogs who Asked for a King"; and "The Jay and the Peacocks".